Um território chamado Florbela - Goor, Iracema (2021)
The present doctoral dissertation consists in an investigation about the territorial construction in the of Florbela Espanca (1894-1930) poetics, based on the concept of “territory” coined by the philosophy of Gilles Deleuze and Félix Guattari. In this regard, it seeks to map the movements and displacements in the poet's production through a visit to her work as a whole, based on the cartography of the types of relations presented in the poems with the earth element. namely: the motherland, the homeland and the earth-body. To follow this line of investigation, the thought of Gilles Deleuze and Félix Guattari worked as a rhizome, constituting an open system for many inputs and outputs, and an intertwining with the intensity of the sensations that permeate the poet's work, aiming present the construction of a multiple territory, which goes beyond the most common vision of a poetics representative of the Alentejo land. The doctoral dissertation is divided into three parts, which correspond to the three chapters of the thesis. In the first, the objective is to build the atmosphere in which the poet's creative process is born, over the Alentejo lands and the relationships that constituted its surroundings. In the second, in order to travel through the Florbela territory, we worked with the poet's first projects, in which the issue of land as a Portuguese culture, and more precisely Alentejo´s culture, was more explicitly present. In the third, we reach a broader approach to the refrain in the Florbelian Constellation, based on reading of more mature poems, in which the earth, nature and culture element expands to the earth-body. The research led us to discover that, in addition to having sung about its land and its people, the poetic territory in Florbela advances towards a spread that does not delimit, does not stop, and advances towards the discovery of new, unrestricted lands. to the homeland and to mother nature, even though intimately related to them